Do patients with rheumatoid arthritis show a different course of COVID-19 compared to patients with spondyloarthritis? - Hasseli-Fräbel, Rebecca; Pfeil, Alexander; Hoyer, Bimba F.; Krause, Andreas; Lorenz, Hanns-Martin; Richter, Jutta G.; Schmeiser, Tim; Voll, Reinhard E.; Schulze-Koops, Hendrik; Specker, Christof; Müller-Ladner, Ulf (Clinical and experimental rheumatology, 2021)
OBJECTIVES: Rheumatoid arthritis (RA) and spondyloarthritis (SpA) are the most common inflammatory rheumatic diseases (IRD). The aim of this study was to elucidate differences in the outcome of SARS-CoV-2 infection in RA- and SpA-patients. - METHODS: Data from the German COVID-19 registry for IRD patients from 30th March to 16th November 2020 were analysed. 208 RA and SpA patients were included in the study, matched for gender and age. - RESULTS: 104 SpA patients (40% patients with ankylosing spondylitis, 54% with psoriatic arthritis and 6% with enteropathic arthritis) were compared to 104 RA patients. For both groups, median age was 56 years. TNF-i treatment was reported in 45% of the SpA and in 19% of RA patients (p=0.001). Glucocorticoids were used in 13% of the SpA and in 40% of the RA patients (p=0.001). In both groups, the majority of the patients (97% SpA, 95% RA) recovered from COVID-19. Hospitalisation was needed in 16% of the SpA and in 30% of the RA patients (p=0.05), and oxygen treatment in 10% and 18% respectively (p=ns). Three versus six (p=ns) fatal courses were reported in the SpA versus the RA group. - CONCLUSIONS: The study revealed that the hospitalisation rate during COVID-19 infection, but not the mortality, was significantly higher in RA as compared to SpA patients. This could be explained either by different treatment strategies or by different susceptibilities of the two diseases.